Features of postural disorders and motivational priorities regarding health activities of women of the first period of adulthood - Igor Grygus; Volodymyr Rebrov; Tetyana Gamma (Kazimierz Wielki University, 2021)
Relevance. There are factors of the physical environment and/or physical conditions of activity, namely, work mode, information flows, working posture at a personal computer, muscle tension, etc. that specialists include into the list of intra-organizational conditions of activity having a negative effect on human health. Most of people who are in the above-described technogenic conditions are restricted in their movements. Research tasks. Determining the features of posture types of women aged 23-27. Studying the motivational priorities of the studied contingent. Determining statistically significant relationships between age, type of posture and socio-pedagogical profile of women of the first period of adulthood. Research results. Only 24.8% of women were found to have normal posture, while the rest suffered from postural disorders, with round back being the most common disorder found of 40.7% of women, associated with excessive curvature of the thoracic spine. A flat back is observed at 26.6% of women, and a scoliotic posture is found of 7.9% of women. It is worth noting that women of the first period of adulthood show a high interest in physical education and sports rehabilitation. The main motivational priorities include the health motive is the most important incentive for the majority of women (62.2%), which indicates their desire to maintain and improve their health. The aesthetic motive ranks second in importance (24.3%), emphasizing the importance of appearance for these women. The emotional motive (10.8%) also has a certain significance, indicating the importance of positive emotions and well-being from classes. Communicative and professional motives occupy lower positions, which may indicate a lower orientation towards social interactions or professional benefits from physical activity. Conclusions. It is determined that time constraints, family responsibilities, and lack of awareness were identified as major barriers for regular physical activity, as married and divorced women may have less time for physical activity due to family responsibilities. The lack of support from the environment can also reduce motivation for physical activities, this is evidenced by the fact that most women (81.08%) prefer classes in physical culture and health groups or sections, and independent classes are not popular among participants.